A study of size effects in bioinspired, "nacre-like", metal-compliant-phase (nickel-alumina) coextruded ceramics. (15th April 2018) - Wilkerson, Ryan P.; Gludovatz, Bernd; Watts, Jeremy; Tomsia, Antoni P.; Hilmas, Gregory E.; Ritchie, Robert O.
Abstract: Coextrusion has been shown to be a viable processing route for the fabrication of bioinspired ceramic materials that exhibit improved damage tolerance. This provides one of the few examples of the synthesis of "nacre-like" ceramic hybrid structures with "brick-and-mortar" architectures using a method that includes the "mortar" ( i.e ., the metallic or polymeric compliant phase) during the entire fabrication process, instead of infiltrating it into a pre-fabricated ceramic scaffold. In this study, we examine how manipulation of filament size can lead to improved mechanical performance in the resulting biomimetic ceramics by reduction of the brick size and mortar thickness while still maintaining a model high volume fraction (∼90 vol.%) ceramic containing a metallic compliant phase. Specifically, we synthesized model brick-and-mortar alumina hybrid structures (Al2 O3 /Ni) containing small volume fractions (<10%) of nickel which we made by the coextrusion of alumina and nickel oxide in a thermoplastic (polyethylene-ethyl acrylate) suspension. Flexural strength and crack-initiation fracture toughness values were used to compare the performance of various ceramic brick sizes, with full crack-growth resistance-curves (R-curves) measured and compared to similar bioinspired ceramics to ascertain how brick size and mortar thickness affect the final mechanical performance. It was found that even though these structures are significantly coarser than those made with other processing methods, they still exhibit comparable crack-growth resistance, despite their lower strength, as well as improving R-curve behavior that tracks closely with brick size. Indeed, these structures display some of the highest fracture toughness values of any high-volume fraction alumina with a metallic compliant phase to date. Toughening was found to be induced by marked crack deflection as the crack path followed the metallic "mortar" phase, coupled with significant crack bridging and "brick" pull-out in the image of the toughening mechanisms seen in nacre. Graphical abstract: The ceramic process method of coextrusion has been used to manufacture bioinspired alumina ceramics in the form of "nacre-like" brick-and-mortar microstructures, where strength is provided by 90 vol.% of alumina bricks whereas ductility is provided by limited inter-brick displacements in a metallic nickel mortar. By refining the already coarse structure resulting from coextrusion, alumina ceramics have been created with high R-curve fracture toughness values exceeding 15 MPam 1/2, although strength levels did not exceed 200 MPa due to cracking in the nickel/alumina interfaces, rather than within the metallic mortar. Image 1